Respostas

2013-12-15T11:01:53-02:00
A)
Δ = b² -4ac
Δ = (-18)² -4 *1 * 0
Δ = 324 - 0
Δ = 324
x' = (-b + √∆)/ 2a
(-(-18) + 18)/2 * 1
(18 + 18)/2
36/2
18
x'' = (-b - √∆)/ 2a
(-(-18) - 18)/2 * 1
(18 - 18)/2
0/2
0

b)
Δ = b² -4ac
Δ = (-256)² -4 *1 * 0
Δ = 65536 -  0
Δ = 65536
x' = (-b + √∆)/ 2a
(-(-256) + 256)/2 * 1
(256 + 256)/2
512/2
256
x'' = (-b - √∆)/ 2a
(-(-256) - 256)/2 * 1
(256 - 256)/2
0/2= 0

c)
3x
²+5=5+2x
3x²-2x=5-5
3x²-2x=0
Δ = b² -4ac
Δ = (-2)² -4 *3 * 0
Δ = 4  - 0
Δ = 4
x' = (-b + √∆)/ 2a
(-(-2) + 2)/2 * 3
(2 + 2)/6
4/6 
x'' = (-b - √∆)/ 2a
(-(-2) - 2)/2 * 3
(2 - 2)/6
0/6
0

d)
4x
²-27=x²
4x²-x²=27
3x²-27=0
Δ = b² -4ac
Δ = 0² -4 *3 * (-27)
Δ = 0 + 324
Δ = 324
x' = (-b + √∆)/ 2a
(-0 + 18)/2 * 3
(0 + 18)/6
18/6= 3
x'' = (-b - √∆)/ 2a
(-0 - 18)/2 * 3
(0 - 18)/6
-18/6
-3
1 5 1
2013-12-15T13:18:15-02:00
Resolva as equaçoes incompletas do 2 grau:
A)x²-18x = 0  
Aplicando a baskara temos x'=18     x" = 0 porque não temos o c
              
B)x²-256 = 0
x² = 256
x = + ou - 16

C)3x²+5 = 5+ 2x  
3x² -2x =0
Aplicando a baskara temos x'= 2/3     x" = 0 porque não temos o c
          
D) 4x² - 27 = x²
4x² - x² - 27 = 0
3x² -27 = 0
x²= 27/3
x²= 9
x = + ou - 3